2004
DOI: 10.1258/0022215041917970
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of modified radical mastoidectomy

Abstract: The primary aim of treatment of cholesteatoma is to attain a dry, safe, stable ear, free of disease. Maintaining or improving hearing is important but the pursuit of a hearing result should not compromise this primary aim. This study reviews the long-term outcome of 133 patients, suffering from advanced disease, who underwent modified radical mastoidectomy between 1995 and 2000. Of these, 49 per cent had had previous mastoid surgery elsewhere. A dry, waterproof ear was attained in 95 per cent of patients. In 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 11 publications
5
23
0
Order By: Relevance
“…It is astonishing that, irrespective of the surgical technique, a dry nonirritated and well-healed ear site was found in accordance with the literature in 93% in our follow-up (6,7,14), particularly because cholesteatoma ears constitute a focus of longstanding chronic infection, often filled with purulent secretion.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is astonishing that, irrespective of the surgical technique, a dry nonirritated and well-healed ear site was found in accordance with the literature in 93% in our follow-up (6,7,14), particularly because cholesteatoma ears constitute a focus of longstanding chronic infection, often filled with purulent secretion.…”
Section: Discussionsupporting
confidence: 89%
“…In the literature, surgical technique is regularly debated, also in having different weighting: some authors primarily pursue the objective of a dry ear with a low rate of recurrence (14,15), whereas others emphasize the importance of functionality, especially in children (7). Various attempts have been made to find a dynamic approach (1,6,10,11,15Y17).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of male to female patients was 1.3:1. Analogous conclusion has been made by Chandra & Mishra 9 , Mukherjee P et al and Hossain MM et al 10 They concluded that the predominant burden of the disease in males was due to their outdoor working habits exposing them for contamination and contagion. Wang HM et al 11 De Vos C et al 12 and reported a female preponderance in their study with the prevalence of 57.9% and 57% respectively.…”
Section: Resultssupporting
confidence: 70%
“…PTEN is a phosphatase that maintains low levels of phosphatidylinositol (3,4,5)-triphosphate (PIP-3) by conversion to PIP-2. If PTEN fails to maintain this homeostasis, PIP-3 levels increase and activate the Akt/PKB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrences are common and many individuals with cholesteatoma undergo multiple operations (3,4). Recurrences, and the need for multiple operations, result in progressively worse hearing deficits and an increased risk of facial nerve paralysis and other complications.…”
Section: Introductionmentioning
confidence: 99%